Angle-resolved Photoelectron Spectroscopy of large Water Clusters ionized by an XUV Comb - Colaizzi, Lorenzo; Ban, Loren; Trabattoni, Andrea; Wanie, Vincent; Saraswathula, Krishna; Mansson, Erik P.; Rupp, Philipp; Liu, Qingcao; Seiffert, Lennart; Herzig, Elisabeth A.; Cartella, Andrea; Yoder, Bruce L.; et al. (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2021, 2021)
Detailed knowledge about photo-induced electron dynamics in water is key to the understanding of several biological and chemical mechanisms, in particular for those resulting from ionizing radiation [1]. While several studies reporting on detailed low-energy electron scattering cross sections in amorphous ice, liquid water and large water clusters [2] and a time-resolved approach to investigate electron scattering in water has been reported [3], such investigations in gas-phase water clusters have shown to be a promising bridge in between the gas and liquid phase, allowing for many technological limitations to be overcome and setting a clear route to perform attosecond-resolved spectroscopy of hydrated molecules. Indeed, extreme ultraviolet (XUV) attosecond pulses may be used to photo-ionize a water sample and to investigate the electron dynamics and transport properties with extremely high temporal resolution [4].
CRIS-Team Scopus Importer:2023-04-20